Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1123/ijsnem.2018-0391
|View full text |Cite
|
Sign up to set email alerts
|

Case Study: Muscle Atrophy, Hypertrophy, and Energy Expenditure of a Premier League Soccer Player During Rehabilitation From Anterior Cruciate Ligament Injury

Abstract: Maintaining muscle mass and function during rehabilitation from anterior cruciate ligament injury is complicated by the challenge of accurately prescribing daily energy intakes aligned to energy expenditure. Accordingly, we present a 38-week case study characterizing whole body and regional rates of muscle atrophy and hypertrophy (as inferred by assessments of fat-free mass from dual-energy X-ray absorptiometry) in a professional male soccer player from the English Premier League. In addition, in Week 6, we al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…To date, establishing nutritional guidelines along this continuum, especially with such diverse injuries (in terms of duration, severity and type), are not available. A recent case study measured energy expenditure of ~3100 kcal/ day during the first 6 weeks of ACL rehabilitation in an elite Premier League player, 159 close to that of outfield players in full training. Given the metabolic demand of tissue/wound recovery processes, staying as close to energy balance as possible and thus avoiding drastic reductions in energy intake, is perhaps the most crucial nutritional aspect during rehabilitation.…”
Section: Minimising Effects Of Deconditioningmentioning
confidence: 99%
“…To date, establishing nutritional guidelines along this continuum, especially with such diverse injuries (in terms of duration, severity and type), are not available. A recent case study measured energy expenditure of ~3100 kcal/ day during the first 6 weeks of ACL rehabilitation in an elite Premier League player, 159 close to that of outfield players in full training. Given the metabolic demand of tissue/wound recovery processes, staying as close to energy balance as possible and thus avoiding drastic reductions in energy intake, is perhaps the most crucial nutritional aspect during rehabilitation.…”
Section: Minimising Effects Of Deconditioningmentioning
confidence: 99%
“…It is clear that the extreme models of disuse described above do not reflect the experiences of athletes during most periods of training restriction. However, case-study data on elite footballers suggest that injury induced periods of disuse (e. g. Anterior cruciate ligament [ACL] surgery) lead to rapid tissue and performance det-riments that reflect the changes seen in laboratory trials (e. g. loss of muscle mass and function, gain in fat tissue and alterations in metabolic rate) [69,70]. Such effects are evident despite 'best practice' in terms of nutritional and physical therapy countermeasures being applied.…”
Section: Potential Changes In Physiological Characteristics In Responmentioning
confidence: 99%
“…Depending on the severity of the sustained injury, time-loss could be substantial, leading to profound de-conditioning effects within the cardiovascular, metabolic and muscular systems. For instance, following ACL reconstruction, athletes' return to sport may range between 16 and 52 weeks (Anderson et al, 2019). Case studies in elite soccer players have reported profound losses in whole body fat-free mass (5.8 kg), as well as in lean leg mass (0.9-1.5 kg) following immobilization and inactivity during this period (Milsom et al, 2014;Anderson et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, following ACL reconstruction, athletes' return to sport may range between 16 and 52 weeks (Anderson et al, 2019). Case studies in elite soccer players have reported profound losses in whole body fat-free mass (5.8 kg), as well as in lean leg mass (0.9-1.5 kg) following immobilization and inactivity during this period (Milsom et al, 2014;Anderson et al, 2019). Moreover, a 4-20% decline in maximal aerobic capacity (VO 2max ) has been reported following 2-8 weeks of physical de-conditioning, owing largely to the decline in blood volume, and consequently stroke volume and cardiac output (Mujika and Padilla, 2001).…”
Section: Introductionmentioning
confidence: 99%